2002
DOI: 10.1002/polb.10199
|View full text |Cite
|
Sign up to set email alerts
|

Polyetherether ketone/polyarylethersulfone blends: Thermal and compatibility aspects

Abstract: The compatibility behavior of polyetherether ketone (PEEK) with poly(ether sulfone) (PES) has been reexamined using differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and extrudate swell measurements. The blends were prepared by both melt‐blending and solution‐blending techniques. The phase behavior of blends is strongly affected by the blending technique used. Blends prepared by solution‐blending are compatible in the entire composition range on the basis of the single composition‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 34 publications
5
32
0
Order By: Relevance
“…Among other interesting properties of PES, are good hydrolytic and thermo‐oxidative stability, high rigidity, and creep resistance. The high T g of PES suggests the polymer as a suitable candidate for developing PEEK‐based blends 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Among other interesting properties of PES, are good hydrolytic and thermo‐oxidative stability, high rigidity, and creep resistance. The high T g of PES suggests the polymer as a suitable candidate for developing PEEK‐based blends 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…However, the strain of EC-g-(PLMA-b-P(LMA-co-THFMA700)) was lower than that of EC-g-P(LMA-co-THFMA700), which may be caused by the phase separation in EC-g-(PLMA-b-P(LMA-co-THFMA700)), leading to poor miscibility between the diblocks. 28,34 But for EC-g-P(LMA-co-THFMA700), LMA section and THEMA section were well organized in random sequence which would improve the miscibility and endow EC-g-P(LMA-co-THFMA700) with a better elongation performance.…”
Section: Effect Of the Side Chain Architecture Of Smps On Mechanical mentioning
confidence: 99%
“…Nandan et al suggested that some chemical reactions occurring during thermal degradation could be responsible for them. [23] The macro-radicals or small radicals from different homo-polymers can form new chemical species, which should give the different activation energy values. …”
Section: Thermal Stabilitymentioning
confidence: 99%